Analisis Faktor-Faktor yang Mempengaruhi Struktur Modal(Studi Empiris Pada Perusahaan Real Estate and Property yang Terdaftar di BEI Tahun 2011-2014) - Masriah, Siti; , Lukman Hakim, SE, M.Si (2016)
The study aims to analyze the influence of asset structure, profitability, Firm size and business risk to capital structure in corporate real estate and property listed in the Indonesia Stock Exchange in 2011-2014either partially or simultaneously.The population of tehe research is the real estate and property firms listed on the Indonesia Stock Exchange on the period of 2011 to 2014. The sampling technique using a purposive sampling and obtained a sample of 30 companies of real estate and propery.Testing this hypothesis using a multiple linier regression analysis. The results of the study indicate that the asset structure did not significantly affect the capital structure. The profitability significant impact on capital structure.Thefrims size does not significantly affect the capital structure. Business risk while significantly affect capital structure. Asset structure, profitability, firm size and business risk has an impact for 76,4% of the capital structure and the rest 23,6% influenced by othe variables not included in this study. Keywords: Asset Structure, Profitability, Firm size, Business Risk and Capital Structure.